2007
DOI: 10.1165/rcmb.2006-0319oc
|View full text |Cite
|
Sign up to set email alerts
|

Unique Uptake of Acid-Prepared Mesoporous Spheres by Lung Epithelial and Mesothelioma Cells

Abstract: Lung cancers, malignant mesotheliomas (MM), and fibrosis are devastating diseases with limited treatment strategies, in part due to poorly-effective drug delivery to affected areas of lung. We hypothesized that acid-prepared mesoporous spheres (APMS) (1-2 microm diameter, 40 A pore size) might be effective vehicles for pulmonary chemotherapeutic drug delivery. To assess this, APMS, chemically modified with different surface molecules (lipid, a linker having a terminal amine group, a thiol group, or tetraethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 33 publications
5
86
0
1
Order By: Relevance
“…The surface area of asbestos fibers and particles was measured using nitrogen gas sorption analysis to allow computation of identical amounts of surface areas of particulates to be added to cells. Fiber and particle size dimensions were determined by scanning electron microscopy (SEM) as described previously (16). In addition, talc was examined using field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM).…”
Section: Characterization Of Mineral Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface area of asbestos fibers and particles was measured using nitrogen gas sorption analysis to allow computation of identical amounts of surface areas of particulates to be added to cells. Fiber and particle size dimensions were determined by scanning electron microscopy (SEM) as described previously (16). In addition, talc was examined using field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM).…”
Section: Characterization Of Mineral Preparationsmentioning
confidence: 99%
“…Cells were grown on Thermonox plastic cover slips (Nalge Nunc International, Naperville, IL), exposed to particulates for 24 hours, and then processed for SEM as described previously (16). After samples were critical point-dried, they were mounted on aluminum specimen stubs and dried before being sputter-coated with gold and palladium in a Polaron sputter coater (Model 5100; Quorum Technologies, Guelph, ON, Canada) and examined on a JSM 6060 scanning electron microscope (JEOL USA, Inc., Peabody, MA).…”
Section: Sem To Determine Particulate/cell Interactionsmentioning
confidence: 99%
“…In vitro cytotoxicity studies suggest that these materials exhibit low toxicity at low concentrations (36)(37)(38)(39)(40)(41) but the toxicity appears to increase at higher concentrations (39). Small amounts of SBA and MCM mesoporous particles have shown little toxicity in in vivo studies (39,42). A good knowledge of the chemistry of mesoporous silicates and their behavior in the human body as well as toxicity tests are an essential requirement for any biomedical applications of these materials.…”
Section: Biocompatibility Biodegradability and Toxicitymentioning
confidence: 99%
“…For instance, a recent in vivo study suggested efficient uptake and biocompatibility of mesoporous silica nanospheres in murine pneumatocytes and mesothelioma cells. 20 In contrast, toxicity of MCM-41 and SBA-15 in mesothelial cells has been reported, eg, intraperitoneal and intravenous injections of either particle produced pulmonary thromboembolic events. 21 Differences in dose, surface area, surface charge, pore diameter, residual reagents, and templates on the materials, as well as route of administration, have all been implicated as potential causes of conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, differences in cellular bioenergetics, cellular uptake, distribution, and other adverse effects have been observed with a variety of mesoporous silica particles prepared by different synthetic methods. 4,15,17,20,21 In addition, the methods used for removing organic templates from mesoporous materials may produce mesoporous materials with different properties, as was discovered recently. 22 Generally, two methods are used to remove the organic templates from these mesoporous materials, ie, high-temperature calcination in air or simple solventwashing (extraction).…”
Section: Introductionmentioning
confidence: 99%